THE INFLUENCE OF THE KOREAN WAVE AND BRAND AMBASSADOR ON PURCHASE INTENTION THROUGH BRAND IMAGE OF THE Y.O.U BRAND IN MAKASSAR CITY - Andi Tenri Fauziyah; Tenri Sayu Puspitaningsih Dipoatmodjo; Ilma Wulansari Hasdiansa; Amiruddin Tawe; Muhammad Ilham Wardhana Haeruddin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Korean culture is increasingly developing and attracting interest in various countries, including Indonesia. The spread of that culture is increasingly supported by the development of technology and information at this time. The Korean Wave has successfully introduced various aspects of its culture through music, drama, and film. There are many factors that can influence purchase intentions, one of which is interest in a particular culture. With the increasing interest in South Korean culture, it has become a new trend for companies in formulating their marketing strategies. The purpose of this research is to determine the influence of the Korean Wave and Brand Ambassador on Purchase Intention through Brand Image. The sample used in this study consists of 120 cosmetic and skincare users in the city of Makassar. Data were processed using the Structural Equation Modeling method. (SEM). The results of this study indicate that (1) the Korean Wave has a direct influence on Purchase Intention, (2) the Brand Ambassador does not have a direct influence on Purchase Intention, (3) Brand Image mediates the relationship between the Korean Wave and Purchase Intention, (4) Brand Image mediates the relationship between the Korean Wave and Purchase Intention, (5) Brand Image cannot mediate the relationship between the Brand Ambassador and Purchase Intention.